The Theme of Social Justice in the Works of Jadid Educators from the Ferghana Valley (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this scholarly article, the author sheds light on the works of Jadid enlighteners from the Ferghana Valley. The article presents ideas about the Jadid ideology of educating people, saving them from ignorance, replacing dogmatic ideas with the true philosophy of religion, improving the education system, and creating a new just society.